2003
DOI: 10.1046/j.1439-0523.2003.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and agronomic evaluation of wheat doubled haploid lines obtained through maize pollination and anther culture methods

Abstract: Although maize pollination (MP) and anther culture (AC) are alternative techniques widely used for wheat doubled haploid (DH) production, there is only limited information on the attributes of the plant materials produced through both methods. This study was conducted to evaluate genetic fidelity, transmission of parental gametes, and to compare field performance of DH populations produced by the MP and AC methods from the F1s of two crosses between spring bread wheat cultivars. The DH populations were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
22
0
1
Order By: Relevance
“…in this manner by doubling chromosomes in haploid plants it is possible to obtain genetically stable homozygous lines in a short time thereby providing a method for speeding up and increasing the selection efficiency. Such homozygous DH plants have been used in breeding programmes for production of pure lines and new highly adaptive and productive varieties (1,4,8,15,16,18,20,21,23,24,35,41,48). A number of studies (2,19,37,45,53,55) also reported that the obtained by the in vitro anther culture techniques haploids and Dh plants are an appropriate system for genetic manipulations, gene mapping and mutant line selection.…”
Section: Introductionmentioning
confidence: 99%
“…in this manner by doubling chromosomes in haploid plants it is possible to obtain genetically stable homozygous lines in a short time thereby providing a method for speeding up and increasing the selection efficiency. Such homozygous DH plants have been used in breeding programmes for production of pure lines and new highly adaptive and productive varieties (1,4,8,15,16,18,20,21,23,24,35,41,48). A number of studies (2,19,37,45,53,55) also reported that the obtained by the in vitro anther culture techniques haploids and Dh plants are an appropriate system for genetic manipulations, gene mapping and mutant line selection.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data shows that wheat DH lines (MP and AC lines) differs in grain yield and some other yield parameters -yield-forming factors (Inagaki et al, 1998;GuzyWróbelska and Szarejko, 2003;Laurie and Snape, 1990). The variation in grain yield between DH lines and parent cultivars could be related to the origin of AC lines (DH androgenic genotypes) as well as MP lines derived from hybrids of F1, and parental cultivars used to hybridization in these experiments (Ma et al, 1999;Guzy-Wróbelska and Szarejko, 2003).…”
Section: Path Analysismentioning
confidence: 89%
“…AC lines compared with MP lines, derived from wheat with maize crosses, yielded lower (Ma et al, 1999) or higher (Guzy-Wróbelska and Szarejko, 2003). Literature data shows that wheat DH lines (MP and AC lines) differs in grain yield and some other yield parameters -yield-forming factors (Inagaki et al, 1998;GuzyWróbelska and Szarejko, 2003;Laurie and Snape, 1990).…”
Section: Path Analysismentioning
confidence: 99%
See 2 more Smart Citations